2015
DOI: 10.3168/jds.2014-9076
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk exosomes contain microRNA and mRNA and are taken up by human macrophages

Abstract: We reported previously that microRNA (miRNA) are present in whey fractions of human breast milk, bovine milk, and rat milk. Moreover, we also confirmed that so many mRNA species are present in rat milk whey. These RNA were resistant to acidic conditions and to RNase, but were degraded by detergent. Thus, these RNA are likely packaged in membrane vesicles such as exosomes. However, functional extracellular circulating RNA in bodily fluids, such as blood miRNA, are present in various forms. In the current study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
291
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(305 citation statements)
references
References 40 publications
10
291
1
3
Order By: Relevance
“…It has been suggested that miRNAs can be transferred from breast milk to the bloodstream (Munch et al 2013;Baier et al 2014;Izumi et al 2015), although these results have also been contested (Laubier et al 2015;Title et al 2015).…”
Section: Controlled Feeding In Piglets Does Not Support Transfer Of Mmentioning
confidence: 95%
“…It has been suggested that miRNAs can be transferred from breast milk to the bloodstream (Munch et al 2013;Baier et al 2014;Izumi et al 2015), although these results have also been contested (Laubier et al 2015;Title et al 2015).…”
Section: Controlled Feeding In Piglets Does Not Support Transfer Of Mmentioning
confidence: 95%
“…Similarly, mEVs from bovine milk were isolated and characterized [13]. Our group demonstrated that bovine mEV contains mRNA and miRNA [14]; thus, mEVs may deliver these RNAs to recipient cells [15]. …”
Section: Introductionmentioning
confidence: 99%
“…In the second scenario, excessive presentation of BTN peptides via dermal and epidermal DCs in the absence of pro-inflammatory signals (IL-12, IL-6, and TNF-a) or co-stimulatory molecules (CD80 and CD86) may lead to T cell anergy (state of unresponsiveness to antigen) after TCR (T cell receptor) stimulation [9]. Simultaneously, extensive incorporation of membrane-bound BTN into neighbor cells' membrane (both non-immune and immune cells) is the other possible mechanism by which BTN-bearing vesicles may contribute to T cell anergy [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 97%